Influence of Acacia catechu Extracts and Urea and Gamma Irradiation on the Mechanical Properties of Starch/PVA-Based Material. (16th October 2012) - Naznin, Marufa; Abedin, Md. Zainul; Khan, Mubarak Ahmad; Gafur, Md. Abdul
Abstract : This work was aimed to study the effect of natural polyphenol extract ( Acacia catechu ) on physicochemical properties of starch/PVA-based film. Acacia catechu extracts were incorporated in the starch/PVA- (60 : 40%) based films at different concentrations (0.1% to 15%) to the total weight of starch/PVA-based film. The tensile strength (TS) of the starch/PVA blend film was 24 MPa and significantly increased (33.8 MPa) by the addition of acacia (0.5%). Different percentages of urea (1% to 15%) were incorporated in the starch/PVA/acacia-based film. The best tensile strength (11 MPa) and elongation at break (59%) were obtained at 5% urea concentration. This 5% urea-incorporated film was irradiated at different radiation doses; the film showed the best results at 100 krad (tensile strength 15 MPa and elongation at break 69%). Molecular interactions due to incorporation of Acacia catechu were supported by FTIR spectroscopy. Thermal properties (TG/DTA) of all the films were carried out successfully. Water absorption trend of all the films was comparatively high. Urea-incorporated film degraded 94%, and irradiated urea incorporated film degraded 91% within 70 days into the soil.